Notes of a potato watcher - Lang, James, 1944- (Texas A & M University agriculture series ;, 2001)
"The potato has a larger story to tell than its humble status suggests. In this account of the potato and its role in human history - and the human future - James Lang tells that story. Combining biology and social science, he describes the origins of cultivated potatoes and how they spread as a staple throughout the world; the many ways to propagate, store, and harvest potatoes; and the crop's potential for feeding a hungry planet. Along the way, Lang also muses on art and agriculture, the stars and ancient peoples, and the cycles of time; he reflects on famine and demography, describes village-based, farmer field schools and looks at the role the potato plays in feeding China."